ANALISIS PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR KECAMATAN LANGOWAN UTARA KABUPATEN MINAHASA - KAMU, SILVA NITA; PATI, AGUSTINUS; SAMPE, STEFANUS (JURNAL ADMINISTRASI PUBLIK, 2020)
Public service delivery; As a consequence of the implementation of Regional Autonomy especiallyafter the enactment of Law Number 23 of 2014 concerning Regional Government. However, various issuesthat arise in the community, apparently the service rights received by the community have not met theexpectations of all parties, both from the general public and from the government itself. In Act Number 25of 2009 concerning Public Services it is stated that public services are activities or series of activities in theframework of meeting service needs in accordance with statutory regulations. Subdistricts are formed inorder to improve the coordination of government administration meaning that with the existence ofSubdistricts, the Camat as the highest leader in the Subdistrict must be able to coordinate all governmentalaffairs in the Subdistrict, then also the Subdistrict must provide public services in the Subdistrict as well asempowering the Village / Kelurahan community. North Langowan Subdistrict is a sub-district organizationthat provides public services to the community which is inseparable from various problems, especially withchanges in various regulations regarding the sub-district. The purpose of this study is to analyze publicservices in the Langowan Utara District in Minahasa Regency.This study uses a qualitative approach as an informant, researchers take 5 (five) people as informantswith snowball technique who are competent to answer the research objectives, through in-depth interviewswhich are then presented and analyzed qualitatively. Moenir (2002: 88), in the implementation of a publicservice, there are several factors that support, namely: employee awareness; There are rules; organizationalactors; Ability and skill factors; Service facility factor. With qualitative data analysis techniques.From the results of research conducted on the implementation of public services using the theory, itappears that the implementation of quality public services is determined between two factors namely internalfactors namely employees, leadership and external factors and rules namely the community, communicationwith the village government and vertical communication with the government districts. In the northernLangowan sub-district, the results of the study carried out public services in accordance with applicableregulations, especially during the co-pandemic period 19.Conclusions from this study In terms of employee awareness in public services it can be concludedthat it is good, the level of employee awareness is influenced by several factors such as leadership, rules anda positive work environment, the availability of rules that support organizational regularity has been ownedby the North Langowan District Office, that the availability of rules is sufficient to help employees,organizational factors in public services in the northern langowan sub-district, it appears that theorganization's readiness is well equipped with existing systems and standard operating procedures (SOPs),the ability and skills of employees in carrying out public services in the sub-district are not evenly distributedand the availability of equipment is available and able to be operated by employees, but the quality ofequipment that is still standard plus knowledge in equipment maintenance causes supporting facilities areeasily damaged and limited quantity causes dependence on the use of equipment only on one or a fewdevices, which then causes delays in service to the communityKeywords: Analysis, Public Services, District